1999
DOI: 10.1159/000026615
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Cytokine Levels in Patients with Acute Depression

Abstract: There is increasing evidence for an association between the alteration of cytokine concentrations in blood and the pathophysiology of depressive disorders. Studies in humans have not investigated CSF cytokine concentrations and their relationship to depressive disorders. This study reports on the association of the CSF concentration of proinflammatory cytokines, IL-1β, IL-6 and TNFα, and major depressive disorders. CSF samples were obtained from 13 hospitalized patients with acute unmedicated severe depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
185
2
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(194 citation statements)
references
References 26 publications
(36 reference statements)
6
185
2
1
Order By: Relevance
“…An extensive and thorough meta-analysis concluded that there was no consistent evidence for elevated IL-1 in the plasma of depressed patients [206]. However, an elevation of CSF IL-1 has been reported in a limited study [207], but this has not yet been confirmed. Nevertheless, it has been argued that sickness behavior in animals may be a model for depression [195][196][197].…”
Section: Implications Of Cytokine-induced Effects On Neuro-transmissimentioning
confidence: 98%
“…An extensive and thorough meta-analysis concluded that there was no consistent evidence for elevated IL-1 in the plasma of depressed patients [206]. However, an elevation of CSF IL-1 has been reported in a limited study [207], but this has not yet been confirmed. Nevertheless, it has been argued that sickness behavior in animals may be a model for depression [195][196][197].…”
Section: Implications Of Cytokine-induced Effects On Neuro-transmissimentioning
confidence: 98%
“…88 According to the sickness behavior hypothesis, the cytokines TNF-a, IL-1 and IL-6 have frequently been investigated in MD. A considerable number of studies showed elevated serum levels of TNF-a 70,86,[89][90][91][92][93] and IL-1b [94][95][96] in depressed patients, whereas only few investigators reported unchanged levels of these cytokines. 97 A study on elevated mRNA levels of TNF-a in peripheral mononuclear cells of depressed patients confirms the majority of findings on elevated serum levels.…”
Section: The Inflammatory Hypothesis Of Depressionmentioning
confidence: 99%
“…98 Levels of IL-1b are also elevated in cerebrospinal fluid (CSF), whereas TNF-a levels are not altered in CSF of depressed patients. 89 As a product of activated monocytes and macrophages, IL-6 is one of the most frequently investigated immune parameters in MD. The majority of reports demonstrate a markedly higher in vitro IL-6 production, 80,94 or higher serum IL-6 levels in depressed patients 65,87,93,[99][100][101][102][103][104] as well as IL-6 mRNA expression in leukocytes.…”
Section: The Inflammatory Hypothesis Of Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of PTX3 is inducible by IL-1b and tumor necrosis factor alpha (TNFa) in the brain , endothelial cells (Breviario et al, 1992), and fibroblasts Lee and Masson, 1993;Diaz et al, 2001). This may be significant given the extensive literature relating depression and immune dysfunction (Leonard, 2000); depressed patients have been shown to have significant elevations of cerebrospinal fluid levels of IL-1b, IL-6, and TNF-a, effects that are antagonized by antidepressants (Levine et al, 1999;Castanon et al, 2002). Although the exact function of PTX3 remains unknown, it has been shown to associate with apoptotic cells.…”
Section: Introductionmentioning
confidence: 99%